Altering Automatic Verbal Processes with Transcranial Direct Current Stimulation - Vannorsdall, Tracy D.; Schretlen, David J.; Andrejczuk, Megan; Ledoux, Kerry; Bosley, Laura V.; Weaver, Jacqueline R.; Skolasky, Richard L.; Gordon, Barry (Frontiers in Psychiatry, 2012)
Abstract Background: Word retrieval during verbal fluency tasks utilizes both automatic and controlled cognitive processes. A distinction has been made between the generation of clusters and switches on verbal fluency tasks. Clusters, or the reporting of contiguous words within semantic or phonemic subcategories, are thought to reflect a relatively automatic processes In contrast, switching from one subcategory to another is thought to represent more controlled, effortful form of cognitive processing. Objective: In this single-blind experiment, we investigated whether tDCS can modify qualitative aspects of verbal fluency, such as clustering and switching, in healthy adults. Methods: Participants were randomly assigned to receive 1mA of either anodal/excitatory or cathodal/inhibitory active tDCS over the left prefrontal cortex in addition to sham stimulation. In the last segment of each 30-minute session, participants completed letter- and category-cued fluency tasks. Results: Anodal tDCS increased both overall productivity and the number and proportion of words in clusters during category-guided verbal fluency, whereas cathodal stimulation produced the opposite effect. Conclusions: tDCS can selectively alter automatic aspects of speeded lexical retrieval in a polarity-dependent fashion during a category-guided fluency task.